Analisis Genangan Banjir Akibat Debit Puncak di DAS Baubau Menggunakan HEC-RAS dan GIS - Nuzul, Muhammad; Achmad, Mahmud; Soma, Andang Suryana (Universitas Diponegoro, Indonesia, 2021)
The history of floods that have occurred in Baubau City from 2009 to 2018 occurred as many as 20 cases, submerging population buildings with a total of 1,206 units. To reduce the impacts that have previously occurred, this study aims to determine the potential flood areas in the Baubau watershed with a return period of 5 to 100 years. The first thing to do is to know the design flood discharge using 10 years of rainfall data analyzed by the Nakayasu Synthetic Unit Hydrograph method. From the results of the field survey data on river hydrological characteristics and watershed morphometric parameters were obtained then analyzed with a hydraulic model using HEC-RAS 5.0.7 software then exported to HEC-GeoRAS is a tool of ArcGis version 10.5. Based on the results of the hydrological model integrated into the hydraulic model in the findings of this study, an estimate of physical, social and economic losses is obtained as well as maps of spatial-based flood potential areas that occur in 3 sub-districts namely Murhum sub-district, Batupoaro sub-district and Wolio sub-district scattered in 7 urban villages through which the Baubau river flows with a high risk class status level.